A "One Pot, " Environmentally Friendly, Multicomponent Synthesis of 2‐Amino‐5‐cyano‐4‐[(2‐aryl)‐1H‐indol‐3‐yl]‐6‐hydroxypyrimidines and Their Antimicrobial Activity. (25th March 2014) - Gupta, Ragini; Jain, Anshu; Madan, Yogita; Menghani, Ekta
<x xml:space="preserve">Abstract</x> A series of multifunctional 2‐amino‐5‐cyano‐4‐[(2‐aryl)‐1H‐indol‐3‐yl]‐6‐hydroxypyrimidines (4a, 4b, 4c, 4d, 4e, 4f) was synthesized by multicomponent reaction of 3‐formylindole (1), cyanoethylacetate (2), and guanidine hydrochloride (3) with NaOH by using green chemical techniques, viz. microwave irradiation and grindstone technology. The same reactants when refluxed in ethanol also gave titled compounds (4a, 4b, 4c, 4d, 4e, 4f). Compared with conventional procedure, the reaction can be carried out under milder conditions, requiring a shorter reaction time and giving higher yields following the green chemistry methodology. All the synthesized compounds have been characterized on the basis of elemental analyses and spectral data (IR, 1H NMR, 13C NMR, and mass). All synthesized compounds were also evaluated for their antimicrobial activity against nine pathogenic bacteria, antifungal activity against Rhizopus stolonifer, Aspergillus flavus, and Fusarium oxysporum and antibacterial activity against Escherichia coli and Pseudomonas aeruginosa at different concentrations. Most of the compounds showed mild to moderate activity.